Functional Outcomes in Survivors of Pediatric Sepsis: A Scoping Review and Discussion of Implications for Low- and Middle-Income Countries - Ravikumar, Namita; Sankar, Jhuma; Das, Rashmi Ranjan (Frontiers in Pediatrics, 2022)
Background Pediatric sepsis is an important cause of mortality and morbidity in low- and middle-income countries (LMIC), where there is a huge burden of infectious diseases. Despite shortage of resources, adapting protocol-based care has reduced sepsis-related deaths but survivors of pediatric sepsis are at risk of poor functional outcomes. Objectives To perform a scoping review of the literature on functional outcomes of pediatric sepsis survivors after discharge from the intensive care unit (ICU) and discuss the implications for patients in LMICs. The outcomes include prevalence of survival with reduced functional outcomes or quality of life (QoL) and changes over time during follow-up or recovery, and these outcomes were compared with other groups of children. Methods We searched major medical electronic databases for relevant literature from January 2005 until November 2021, including Medline (via PubMed), Embase, CINAHL, and Google Scholar databases. We included observational studies and follow-up data from clinical trials involving children/adolescents (≤18 years) who were admitted to pediatric intensive care unit (PICU) and got discharged finally. Major focus was on survivors of sepsis in LMIC. We followed PRISMA guidelines for scoping reviews (PRISM-ScR). Results We included eight papers reporting data of functional outcomes in 2,915 children (males = 53%, and comorbidity present in 56.6%). All included studies were either a prospective or retrospective cohort study. Studies were classified as Level II evidence. Disabilities affecting physical, cognitive, psychological, and social function were reported in children following discharge. Overall disability reported ranged between 23 and 50% at hospital discharge or 28 days. Residual disability was reported at 1, 3, 6, and 12 months of follow-up with an overall improving trend. Failure to recover from a baseline HRQL on follow-up was seen in one-third of survivors. Organ dysfunction scores such as pSOFA, PeLOD, vasoactive inotrope score, neurological events, immunocompromised status, need for CPR, and ECMO were associated with poor functional outcome. Conclusions The research on functional outcomes in pediatric sepsis survivors is scarce in LMIC. Measuring baseline and follow-up functional status, low-cost interventions to improve management of sepsis, and multidisciplinary teams to identify and treat disabilities may improve functional outcomes.